Chiral separation and spectroscopic characterization of mefloquine analogues - Dobšíková, K; Kohout, M; Setnička, V (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2025)
Mefloquine, a widely used antimalarial agent, has spurred ongoing research into the development of derivatives with enhanced efficacy and reduced side effects. In this investigation, we synthesized two compounds containing N-allyl or N-tert-butylacetamid groups. A chiral liquid chromatography with polysaccharide chiral stationary phase was utilized to separate the enantiomers of both derivatives. We employed spectroscopic chiroptical and non-polarizable methods such as electronic and vibrational circular dichroism, infrared absorption and ultraviolet spectroscopies. Combined with density functional theory calculations, the stable conformers were found in solution and their spectra were subsequently simulated. We elucidated the three-dimensional structure of the enantiomerically pure compounds and assigned the absolute configuration of all prepared derivatives using both experimental and simulated spectra.
Keywords: DFT calculations; Chiral liquid chromatography; Mefloquine; Circular dichroism